Motives for practice of physical activities: an evolutionary approach - Hsu, Rafael Ming Chi Santos (2021)
Introduction: Motivation studies are key to foster behaviors that can be crucial to health, such as physical activity (PA). Despite its known benefits, a great proportion of the population does not practice PA regularly. One way to understand such an issue can be through an evolutionary analysis regarding motives for PA practice, which takes into account different priorities chosen by different participants. Some hypotheses focusing on survival value were proposed to explain sex differences in motivation for sports, such as Allying with Coalitions (more social motives in men) or Socialization (more appearance motives in women), however, there is a lack of evolutionary oriented studies analysing classification systems of PA. Previous classifications can be questioned because of lack of theoretical support or lack of statistical criteria. In addition, better understanding of how these variables are related may improve interventions regarding health promotion. Aims and Predictions: We aimed to explore individual differences in motives for practice of different types of physical activities and other related variables, through self-reported questionnaires. Specifically, we compared different PA classification systems according to 5 subscales of motivation for PA (Interest/Enjoyment, Competence, Appearance, Social, Fitness/Health) using 4 categories of PA (Individual Sports, Collective Sports, Exercises, Body/Movement Practices- Chapter One), and using previous authors categories, such as Motor Orientation (Water Practices, Rhythmicity, Combativeness) or no categories, i.e., a more data-driven approach (Chapter Two). We also tested if physically active participants differ from sedentary ones in personality (Big Five and self-esteem), sociosexuality and self-reported attractiveness and health (Chapter Three). We expected, for example, that motives for physical activity linked to appearance would be stronger in women, whilst motives linked to sociability would prevail in men. Regarding PA type, we expected a unique profile regarding Body/Movement Practices, showing a pattern of motives distinct to the well described Sports-Exercises dichotomy. Considering the categories of previous authors or the data-driven approach, we expected some emerging peculiarities that could boost discussion in the fields of Physical Education/Sports Sciences/Psychology of Physical Activities. Regarding personality and sociosexuality, we predicted that physically active participants would score higher on extraversion, conscientiousness, openness, self-esteem, self-rated attractiveness and health, sociosexual behavior and lower on neuroticism than sedentary participants. Materials and Methods: We recruited online more than 2,652 participants, mainly university undergraduates, who filled in a battery of questionnaires, including sociodemographic data, motives for physical activities, and measures of personality (Big Five, narcissism, self-esteem) and sexuality (sociossexuality). Main Results: Chapter One- We found main effects of type of PA in all motivations subscales, and of sex on Interest/Enjoyment (higher scores in females). Exercises were the most extrinsically motivated (appearance and fitness/health), while Collective Sports (followed by Individual Sports) were the most intrinsically motivated (interest/enjoyment and competence), and also by sociability. Body/Movement Practices followed an intermediate pattern, generally closer (without significant differences) to Individual Sports compared to other types of PA. Chapter Two: we found that some PAs consistently separated themselves from others regarding motivational subscales. For example, Walking participants showed less Interest/Enjoyment and Competence than several other PAs. Pilates was highlighted by a particular low Social motivation in comparison to other PAs. Regarding the categories of previous authors, results mainly showed that different classification systems in general presented a similar distinction regarding most extrinsic and intrinsic motives. Chapter Three: we found significant more differences among females regarding personality (e.g., physically active women scored higher on extraversion, agreeableness and conscientiousness than sedentary), while among males on sociosexuality (physically active men scored higher than sedentary on both sociossexual attitude and behavior). Some variables showed a similar pattern for both sexes, such as physically active individuals scored higher than sedentary on self-rated health and self-esteem. Important effects of time of practice were noted. Discussion: Our three studies bring important contributions to the related fields, by providing initial evidence toward possible new methods of grouping PA types which can better inform interventions aimed to improve maintenance behavior, using motivation as a grouping factor. Also, important distinctions able to support interventions were found regarding physically active and sedentary regarding self-esteem, personality and sociosexuality, with specific differences according to sex, and time of practice. Conclusions: With our studies, we highlight some important implications regarding interventions in public health through promotion of PAs. Although several improvements can be made in future studies, our proposed classification- Physical activity divided into categories of Sports, Exercises or Body/Movement Practices is coherent, using the motivational oriented analysis. Our other studies also show the potential for further classification systems, and highlight the importance of paying attention to individual differences and types of motives. We further show a manner in which physical activities are related in domains central to human well-being, social interactions, and sexual life. More evolutionary and interdisciplinary based research on PAs is needed